Florida Dairy Farm Situation and Outlook 2008 - Russ Giesy; Albert De Vries; Jay Giesy (EDIS, 2008)
AN200, a 4-page fact sheet by Russ Giesy, Albert De Vries, and Jay Giesy, describes the situation, outlook, and challenges and opportunities for Florida dairy production in 2008. Published by the UF Department of Animal Sciences, July 2008.